Implementasi Peraturan Bupati Nomor 47 Tahun 2021 tentang Santunan Kematian Bagi Masyarakat Miskin di Kabupaten Bojonegoro - Safira, Nadia Ismi; Tukiman, Tukiman (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
Indonesia is one of the developing countries with a fairly high poverty problem. In this problem, the government solves the main problem, namely poverty in the form of policy programs to meet the needs for the welfare of the community. With the high poverty rate, the Bojonegoro Regency Government provides a program as a sense of government concern for the people of Bojonegoro. This program is intended as a manifestation of the responsibility of local governments to improve community welfare equally. The purpose of this study is to determine the extent of the implementation of the death benefit program in Bojonegoro Regency. This research uses a qualitative approach, where the data obtained comes from interviews, observations and documentation as the main source, while secondary data comes from relevant books and scientific articles.The result of this study is that the implementation of the death benefit program is still not fully running optimally. There are implications, especially in terms of socialization and changes in the system to online implementation of the program. Keywords: Policy Implementation, Poverty, Social Security Death